The Teachers' Strategy in Managing Class at Grade IV SD 01 Ulak Karang Selatan - Yona Syaida Oktira; Mardatul Silva; Nadila Rahmawati; Yesi Rasnita Sari; Retno Yulianda; Elvina Lisa (The Future of Education Journal, 2023)
This study aims to describe the classroom teacher’s strategy in managing classes in elementary schools. This research was conducted at SD Negeri 01 Ulak Karang Selatan on May 25 2023. The data from this study were obtained through interviews with class teachers whose results were supporting data from the main source as well as observations about classroom management.The results of the study show that regarding the teacher's strategy in managing classes in elementary schools, that the homeroom teacher for class IV is good at managing the class, this is evidenced by the condition of the classrooms which are well written and neat. By making the class full of student work and prioritizing student activity during the teaching and learning process, students also take part in maintaining the beauty of the class. To regulate air circulation so that it does not interfere with the learning process, the windows are kept open and the air vents are cleaned every day